Pengaruh Pemanasan Berulang Media Nutrient Agar Terhadap Hasil Uji Sensitivitas - Elisa Rinihapsari; Benaya Yamin Onesiforus; Samuel Marchel Nugroho (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Nutrient agar media is a universal medium that can be used in bacterial sensitivity tests. Sensitivity testing is used to test the sensitivity of bacteria to a type of antibiotic. This test is instrumental in determining appropriate therapy for patients who experience recurrent or persistent infectious diseases. Nutrient Agar media is usually made in large quantities for time and energy efficiency. The media is used as needed, and the rest is stored 2-8oC in the refrigerator before being used again. This research aims to determine the effect of repeated heating of Nutrient Agar media on the sensitivity test results for Staphylococcus aureus and Escherichia coli bacteria. Tests were carried out on the first, second, third and fourth heating times. The results of statistical tests with Kruskal Wallis showed a sig value of <0.05, meaning there was a difference in sensitivity test results between media heated once, twice, three times, or four times for the two types of bacteria tested.